EDUKASI TENTANG PENCEGAHAN KECURANGAN KEUANGAN (FRAUD) BAGI PELAKU UMKM - Sandag, Eltie Christi; Durya, Ngurah Pandji Mertha Agung; Shifa, Mutiara; Hasan, Wahyudin; Saprudin, Saprudin (Jurnal Abdimas Bina Bangsa, 2025)
Micro, Small and Medium Enterprises (UMKM) play an important role in the national economy. However, this sector often faces challenges related to financial management, especially in preventing financial fraud. Lack of understanding about transparent and systematic financial management can increase the risk of irregularities, which in turn can harm the UMKM business itself. This community service activity aims to provide education to UMKM players regarding the prevention of financial fraud through the application of good financial governance principles. The method used in this activity is an educational approach based on training and mentoring, which involves counseling sessions, interactive discussions, and simulations of implementing a transparent and accountable financial recording system. This activity was carried out in rural areas by involving a number of UMKM actors from various business sectors. The results of this activity showed an increase in participants' understanding of the types of financial fraud, the factors that cause it, and prevention strategies, including the implementation of a simple internal control system that can be applied according to the scale of their business. With this education, it is hoped that UMKM players will be more aware of the importance of good financial management and be able to implement fraud prevention measures in their business operations.